Assistance with Preparing Financial Reports for Toko Online Aneka in Malang City - Flavian Naretius Gunawan; Jerri Benardus; Marcelino Andrew; Rhenaldy Pius Wicaksono; Setia Andrew Nugraha; Rino Tam Cahyadi; Fitri Oktariani; Bagas Brian Pratama; Audito Aji Anugrah (Journal of Community Practice and Social Welfare, 2024)
Toko Online Aneka is a micro, small, and medium enterprise (MSME) operating in social media markets and selling various types of goods. However, the business has not fully implemented an appropriate financial accounting system, particularly in the area of record-keeping. Therefore, this community service project aims to help Toko Online Aneka improve its financial records. The implementation method involves interviews and direct observation, using primary data from a startup business like Toko Online Aneka. During the mentoring process, the required information and data are obtained from the business owners and individuals directly involved in operations. The output of this service activity is the creation of transaction templates and financial reports. The presence of these templates is expected to help Toko Online Aneka track sales and profits, both on a monthly and annual basis.